From Bedside to Algorithms: The Emerging Role of Nurses in the AI Era - AL MALAQ, MONA HUSSEIN MOHAMAD; AL-GARNI, SAMIRAH TURKEY AHMAD; ALKATHIRI, MAJED HAIDAR AHMAD; ALMALKI, FAISAL DHYFALLAH; ALANAZI, SANAA SALEM; HAYYAN, ASMAHAN MOHAMMED; ALNAZGHAH, ZAHRA HASSAN ABDALLAH; ALNAZGHAH, ZAINAB HASSAN; ALTHAHEB, AFAF ALI IBRAHIM; ALQUDAIHI, RABAB ABDULAZIZ; et al. (Journal of Posthumanism, 2024)
Nursing has always been at the heart of healthcare, rooted in compassion, bedside presence, and hands-on care. Historically, nurses have been the mediators between medical science and human experience, ensuring patients receive not only treatment but also empathy. With the 21st century’s technological revolution, artificial intelligence (AI) has begun to alter this balance. No longer confined to laboratories or high-level diagnostics, AI is entering daily clinical routines, promising to reshape nursing roles. The journey “from bedside to algorithms” blends caregiving with computational intelligence.